PENCEGAHAN PENYAKIT SISTEMIK PADA INFEKSI TINEA UNGUIUM KUKU PETANI DESA TRAGAH KABUPATEN BANGKALAN - Dwi Aprilia Anggraini; Norma Farizah Fahmi (STIKES NGUDIA HUSADA MADURA, 2022)
Tinea unguinum is a common condition that begins as a yellow spot or spot under the tip of the fingernail or toenail. A severe fungal infection can cause the nail to blacken, thicken, and crumble at the edges. This infection can affect some nails but usually not all nails are infected. If the fungal infection of the nail is still relatively mild, it does not require treatment. But sometimes a nail fungus infection can cause pain and thickening of the nail that requires treatment and medication. Nail infections can attack someone who works or is in direct contact with a humid and dirty environment such as farmers and. Farming is one of the livelihoods of the people in Tragah Village, Bangkalaan Regency. Farmers work in the fields/fields that are in contact with soil, water and mud for a long time without using gloves and boots to protect their hands and feet from soil, water and mud so that the hands and feet of farmers are moist and even farmers rarely pay attention to the cleanliness of their nails so that they often leave the toenails on the thumb filled with dirt and the fingernails turn dark, thickened, the nails are barely shaped like normal even some of the growers have a foul smell. From the problem seen, the writer suspects that the farmer's nails are infected with fungus. The purpose of this study is to determine the fungal infection that causes systemic disease. The research method used in this study is descriptive by using a systematic random sampling technique of 150 respondents and 30 samples were used. The method of examination used mushroom culture.